Studi Kitab Tafsir Tanwir Al-Miqbas Min Tafsir Ibni ‘Abbas oleh Al-Fairuzabadi - Hikmah, Farisa Aliyatul; Dahliana, Yeti; Nirwana, Andri; Suharjianto, Suharjianto; Azizah, Alfiyatul; Rha’in, Ainur (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2024)
Tanwir al-Miqbas min Tafsir Ibni ‘Abbas by Al-Fairuzabadi is a classical tafsir (Quranic exegesis) that compiles the interpretative methodology of Ibnu ‘Abbas and offers a unique perspective in tafsir studies. This study aims to deepen understanding of the interpretative methodology in